A mikrotörténelmi módszer és a Selyemút kutatása - Microhistory and Silk Road Studies - FELFÖLDI, Szabolcs (Belvedere Meridionale, 2014)
Doing research on one of the most important trading routes of the antiquity and the middle ages, namely the Silk Road is a very complex task today. We have more information about the Silk Road than ever before; our knowledge is more comprehensive, so this special commercial system seems to be more complicated as well. It is an obvious question, therefore, what methods can be used to examine more precisely its intrinsic characteristics. This article discusses the question whether one of the newest methods of historical science, i.e. microhistory or history of everyday life, can be applied in the case of Silk Road studies. First of all, I have given a brief overview of the development of microhistory and its perception in Hungary. Secondly, I have determined its techniques and research questions. As microhistory examines the small units of history, such as single events, persons, families or communities, I have considered it as an adequate and innovative method to investigate the complex historical problems of the Silk Road.